Diverse but desolate landscape of gut microbial azoreductases: A rationale for idiopathic IBD drug response. (31st December 2023) - Simpson, Joshua B.; Sekela, Josh J.; Carry, Benjamin S.; Beaty, Violet; Patel, Shakshi; Redinbo, Matthew. R.
ABSTRACT: Prodrugs reliant on microbial activation are widely used but exhibit a range of efficacies that remain poorly understood. The anti-inflammatory compound 5-aminosalicylic acid (5-ASA), which is packaged in a variety of azo-linked prodrugs provided to most Ulcerative Colitis (UC) patients, shows confounding inter-individual variabilities in response. Such prodrugs must be activated by azo-bond reduction to form 5-ASA, a process that has been attributed to both enzymatic and non-enzymatic catalysis. Gut microbial azoreductases (AzoRs) are the first catalysts shown to activate azo-linked drugs and to metabolize toxic azo-chemicals. Here, we chart the scope of the structural and functional diversity of AzoRs in health and in patients with the inflammatory bowel diseases (IBDs) UC and Crohn's Disease (CD). Using structural metagenomics, we define the landscape of gut microbial AzoRs in 413 healthy donor and 1059 IBD patient fecal samples. Firmicutes encode a significantly higher number of unique AzoRs compared to other phyla. However, structural and biochemical analyses of distinct AzoRs from the human microbiome reveal significant differences between prevalent orthologs in the processing of toxic azo-dyes, and their generally poor activation of IBD prodrugs. Furthermore, while individuals with IBD show higher abundances of AzoR-encoding gut microbial taxa than healthy controls, the overall abundance of AzoR-encoding microbes is markedly low in both disease and health. Together, these results establish that gut microbial AzoRs are functionally diverse but sparse in both health and disease, factors that may contribute to non-optimal processing of azo-linked prodrugs and idiopathic IBD drug responses.